A system's model of scaling: leveraging upon centralised and decentralised structures for diffusion. Issue 2 (2nd July 2016) - Hung, David; Jamaludin, Azilawati; Toh, Yancy; Lee, Shu Shing; Wu, Longkai; Shaari, Imran
ABSTRACT: A key thrust of education reform is the spread of innovative ideas and practices oriented toward school improvement and advancements in student's deep learning and teacher's professional development. Framed within concepts of scaling and diffusion, trajectories of innovation spread can afford explanatory and predictive understandings of adoption or rejection of new ideas and practices. This paper seeks to trace and unpack the adoption and adaptation trajectories of innovative pedagogical practices facilitated by technologically-mediated innovations within the context of Singapore schools. Recognising the Singapore education system as affording both centralised structures (in terms of shared responsibility and accountability across the education ministry, teacher training institute, and schools) and decentralised tenets (in terms of manoeuvrability, autonomy and agency for schools on the ground to chart their own innovation path), the research (1) characterises the variant models of innovation spread within a context of innovations in Singapore, (2) explicates how such models leverage on the centralised-decentralised structures of the system, and (3) draws implications for "harvesting" of innovations for rootedness and sustainability in schools.